Electrical safety in low voltage distribution systems up to 1 000 V AC and 1 500 V DC. Equipment for testing, measuring or monitoring of protective measures. Power metering and monitoring devices (PMD) Part 12, (28th June 2022) - British Standards Institution
No abstract available